Cutting the credit line: Evidence from Germany - Stefan Goldbach; Volker Nitsch (Deutsche Bundesbank, 2015)
The massive decline in international trade in 2008/09 is often attributed to the global deterioration in financial conditions after the bankruptcy of a US investment bank, Lehman Brothers. This paper examines the association between external finance and firm activity in Germany in more detail. In particular, we explore a novel data set that matches a full sample of quarterly bank-firm lending data with detailed information on borrowers and lenders. Our results indicate that foreign sales are insensitive to variations in external finance. While German banks affected by the crisis have significantly reduced their credit supply, we only observe a causal (negative) effect on domestic sales. Exporting firms, in contrast, seem to be particularly good borrowers.
Keywords: E44; E32; G21; F40; 330; trade finance; export finance; relationship lending